Avaliação da capacidade funcional em pacientes pós-covid-19 com queixas de fadiga - RODRIGUES, Ana Flávia Café (2024)
Long COVID syndrome has been the subject of study to better understand fatigue as a recurring complaint with an impact on the quality of life in patients with post-covid syndrome. This work aimed to evaluate the intensity and frequency of fatigue symptoms and daily limitations in patients who developed long Covid. A cross-sectional, descriptive and analytical study was carried out at the Tropical Medicine Center. The Fatigue Assessment Scale (EAF) and clinical epidemiological questionnaire were applied to identify variables associated with fatigue, the data were analyzed by main components, the reliability of the scale was also evaluated using the Cronbach's alpha (α) Reliability test. The comparison of the level of fatigue and the presence or absence of personal morbid history was analyzed using the Student's t test, the Fisher's Exact test was used to evaluate the relationship between independent variables (gender and comorbidities) with the main components with the greatest weight. . 61 patients were evaluated with a mean age of 55.4 ± 12.2, with a predominance of females (82%), regarding comorbidities, 80.3% of patients had at least one comorbidity. The analysis of the main components of the EAF revealed moderate reliability, with the most important components identified as "Fatigue bothers me", with 42.3%, and "I get tired quickly", with 13.16%. It was observed that physical and psychological domains are associated with more intense experiences of fatigue in long-term COVID-19 syndrome. The presence of comorbidities was not associated with the intensity of fatigue. It was concluded that Long COVID syndrome is a clinical challenge, fatigue is a frequent complaint, and may be more frequent in women, but it was not associated with the comorbidities evaluated, suggesting that fatigue is the result of mechanisms inherent to virus infection.